Neutral current electroweak interactions and the structure of the proton - Borner, H; Borner, Harald Peter Wilhelm Jochen (1990)
﻿ In this thesis we investigate the scattering of neutrinos and antineutrinos off free protons in the deep inelastic region via the neutral weak current. In the BEBC experiment, a hybrid detector consisting of a large liquid hydrogen bubble chamber and electronic counters for muon and hadron identification, has been exposed to the CERN wide band beam of neutrinos with energies up to 300 GeV. The detector provides the possibility to discriminate efficiently between hadron-induced and neutrino-induced muonless events. We are interested in the structure of the proton as it is resolved by the neutral carrier Zº of the electroweak force. The kinematical scaling variable X(BJ) that represents information about the proton structure cannot be reconstructed in an experiment using a hydrogen target. Thus the X(BJ) dependence of the cross section for free protons has so far not been accessible. We construct a method that links the measurable distribution in a new variable w1 that incorporates the hadronic momentum longitudinal and transverse to the beam, to the one in X(BJ), in a model-independent way. It is shown that even with the statistics of about a thousand events it is possible to recover the X(BJ) dependence fo the neutrino proton cross-section with appreciable precision. This method is then applied to the data that consists of 2200 neutrino and 1060 antineutrino neutral current events, after correcting for various backgrounds and cuts. We observe a neutral current proton structure that is consistent with the notion of parton universality. The results are compared to two other investigations which employ isoscalar heavy targets, and we find agreement in as far as they are comparable. Furthermore we study the connection between the neutral current structure functions and distributions in the hadronic scaling variable w. It is found that they are related by simple formulae which do not incorporate any dependence on further kinematical variables, in the scaling approximation. We advocate the use of the w dependence of the neutral current cross section as an important piece of information that can provide access to some quantities that are measured only indirectly in charged current and electromagnetic scattering, and to the behaviour of the structure functions at small values of their argument.